2010
DOI: 10.1007/s00253-010-2768-z
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of β-1,4-glucosidase from Agaricus arvensis onto functionalized silicon oxide nanoparticles

Abstract: An efficient β-1,4-glucosidase (BGL) secreting strain, Agaricus arvensis, was isolated and identified. The relative molecular weight of the purified A. arvensis BGL was 98 kDa, as determined by sodium dodecylsulfate polyacrylamide gel electrophoresis, or 780 kDa by size exclusion chromatography, indicating that the enzyme is an octamer. Using a crude enzyme preparation, A. arvensis BGL was covalently immobilized onto functionalized silicon oxide nanoparticles with an immobilization efficiency of 158%. The appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 24 publications
5
52
1
Order By: Relevance
“…This increase of optimum temperature range may be due to conformational stability of the enzyme (Wang et al 2011). Singh et al (2011) also observed that the optimum temperature of the free b-glucosidase, isolated from Agaricus arvensis was 65°C, but the b-glucosidase immobilized on SiO 2 nanoparticles had maximal activity at 70°C. They also observed that for the free enzyme, increase in temperature resulted in a sharp decrease in the relative activity of the free enzyme.…”
Section: Ph and Temperature Optima Of Free And Immobilized B-glucosidasementioning
confidence: 89%
See 4 more Smart Citations
“…This increase of optimum temperature range may be due to conformational stability of the enzyme (Wang et al 2011). Singh et al (2011) also observed that the optimum temperature of the free b-glucosidase, isolated from Agaricus arvensis was 65°C, but the b-glucosidase immobilized on SiO 2 nanoparticles had maximal activity at 70°C. They also observed that for the free enzyme, increase in temperature resulted in a sharp decrease in the relative activity of the free enzyme.…”
Section: Ph and Temperature Optima Of Free And Immobilized B-glucosidasementioning
confidence: 89%
“…They also observed that for the free enzyme, increase in temperature resulted in a sharp decrease in the relative activity of the free enzyme. In contrast, the immobilized enzyme showed no such tendency and retained 82 % of its optimum activity even at 85°C (Singh et al 2011). …”
Section: Ph and Temperature Optima Of Free And Immobilized B-glucosidasementioning
confidence: 92%
See 3 more Smart Citations